Parental feeding practices and stunting status among preschool children - Aiyzah Okta Viayani; Triani Rahmadewi; Siti Arifah (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Stunting is a condition of growth failure in children caused by chronic malnutrition, characterized by a height-for-age (HFA) score below -2 SD according to WHO standards. An inappropriate diet is one of the factors that can influence the incidence of stunting in preschool-aged children. Stunting is not just a short-term health problem but also disrupts brain development, intelligence, immunity, and increases the risk of chronic diseases in adulthood. Children who are stunted experience limitations in learning, motor skills, and socio-emotional development, which lowers the quality of human resources. Therefore, stunting is a serious public health problem that requires immediate intervention. Purpose: To examine parental feeding practices and stunting status among preschool children. Method: This study employed a quantitative method with a cross-sectional design. The study sample consisted of 36 respondents selected using total sampling. Dietary data were collected using the Child Feeding Questionnaire (CFQ), while the prevalence of stunting was measured by height using a microtoise and calculated based on the height-for-age (HAZ) indicator according to WHO standards. Data analysis was performed using univariate and bivariate methods, employing Fisher’s Exact test with a significance level of α = 0.05 Results: The results of the Fisher’s Exact test show a p-value > 0.05. Based on the results of research conducte, it can be concluded that the eating patterns of preschool children are entirely in the appropriate category (100%), the incidence of stunting mostly does not occur, with 96.7% of children not stunted and only 3.3% experiencing stunting, and there is no relationship between eating patterns and the incidence of stunting in preschool children at both kindergartens (p value = 0.942). Conclusion: These findings suggest that adopting a dietary pattern that considers the type, quantity, and frequency of food is a crucial aspect in supporting the growth and development of preschool-aged children. A balanced and regular diet plays a role in meeting children's nutritional needs, although stunting can still be influenced by other long-term, multifactorial factors. Suggestion: It is recommended for parents and the school to continue maintaining the child's good eating habits and to increase periodic monitoring of nutritional status so that the risk of stunting can be prevented as early as possible.